CRE promoter sites modulate alternative splicing via p300-mediated histone acetylation - Dušková, Eva; Hnilicová, Jarmila; Staněk, David (RNA biology, 2014)
Histone acetylation modulates alternative splicing of several hundred genes. Here, we tested the role of the histone acetyltransferase p300 in alternative splicing and showed that knockdown of p300 promotes inclusion of the fibronectin (FN1) alternative EDB exon. p300 associates with CRE sites in the promoter via the CREB transcription factor. We created mini-gene reporters driven by an artificial promoter containing CRE sites. Both deletion and mutation of the CRE site affected EDB alternative splicing in the same manner as p300 knockdown. Next we showed that p300 controls histone H4 acetylation along the FN1 gene. Consistently, p300 depletion and CRE deletion/mutation both reduced histone H4 acetylation on mini-gene reporters. Finally, we provide evidence that the effect of CRE inactivation on H4 acetylation and alternative splicing is counteracted by the inhibition of histone deacetylases. Together, these data suggest that histone acetylation could be one of the mechanisms how promoter and promoter binding proteins influence alternative splicing.
Keywords: HeLa Cells; Integrases; Acetylation; Fibronectins; reportérové geny; lidé; HeLa buňky; Gene Knockdown Techniques; messenger RNA; integrasy; RNA, Messenger; fibronektiny; protein p300 asociovaný s E1A; genový knockdown; alternativní sestřih; histony; Histones; promotorové oblasti (genetika); Alternative Splicing; Genes, Reporter; Promoter Regions, Genetic; E1A-Associated p300 Protein; acetylace; Humans